Women's Voice and Agency : The Role of Legal Institutions and Women's Movements - de Silva de Alwis, Rangita (World Bank, Washington, DC, 2014)
Global events like the Beijing Women s Conference of 1995 have resulted in the creation of strong international frameworks that set standards for women s rights around the world. Convention on the Elimination of All Forms of Discrimination against Women (CEDAW), the Beijing Platform for Action, and other international norms define the scope of universal rights for women and girls, and have opened new spaces for regional and national legal reform. Bottom-up engagement with these international laws and institutions by local and transnational women s movements has catalyzed widespread changes in lawmaking and transformed standard-setting documents into tools for reform. The following paper discusses four important pillars of women s voice and agency (while recognizing that there are others which are beyond the scope of this review): freedom from the risk of violence; freedom of movement; freedom to make decisions on family formation and the freedom to shape policy. It will examine the ways in which these freedoms impact women s voice and the ways in which women are working to reform law and policy to ensure these four freedoms are accessible to all.